2020
DOI: 10.1002/ncp.10586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gastrostomy Tube Feeding Education on Parents of Children with Gastrostomy

Abstract: Background Success in long‐term enteral feeding is, in part, dependent on careful selection of the appropriate enteral access device and placement technique together with proper maintenance and care. This study was conducted to evaluate the effect of education on satisfaction with gastrostomy tube feeding, quality of life, caregiver burden, and anxiety. Methods A quasi‐experimental, pretest and posttest research design without a control group was used. A total 78 mothers were included in the study. The child a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…They showed that the QoL from these caregivers was below the average of the general population (moderate hopelessness in 20%, moderate and severe anxiety in 33.3% and moderate and severe depression in 46.7%); however, their results were very similar to those found in other studies that evaluated caregivers of paediatric patients with cerebral palsy that were not using gastrostomy tube feeding, suggesting that the presence of the gastrostomy did not negatively interfere with the caregiver's QoL (97). The importance of gastrostomy tube feeding education in mothers of children with a gastrostomy may increase positive and decrease negative outcomes for these caregivers during the first 3 months post gastrostomy placement using validated questionnaires (98).…”
Section: Quality Of Life Of Children With Gastrostomy and Jejunal Tubesmentioning
confidence: 99%
“…They showed that the QoL from these caregivers was below the average of the general population (moderate hopelessness in 20%, moderate and severe anxiety in 33.3% and moderate and severe depression in 46.7%); however, their results were very similar to those found in other studies that evaluated caregivers of paediatric patients with cerebral palsy that were not using gastrostomy tube feeding, suggesting that the presence of the gastrostomy did not negatively interfere with the caregiver's QoL (97). The importance of gastrostomy tube feeding education in mothers of children with a gastrostomy may increase positive and decrease negative outcomes for these caregivers during the first 3 months post gastrostomy placement using validated questionnaires (98).…”
Section: Quality Of Life Of Children With Gastrostomy and Jejunal Tubesmentioning
confidence: 99%
“…Although CIC is widely recognized as the most effective method used by caregivers for patients who are unable to empty their bladder independently, there is a paucity of literature on the frequency of CIC use in both Turkey children's care can increase caregiver anxiety levels. [15][16][17] Based on this identified problem, the results of this study aimed to discuss the anxiety levels of caregivers who perform CIC on their children and the factors influencing these levels. According to the findings, all caregivers were women, mostly mothers of the children, and the children were mostly diagnosed with SB.…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐established that caregivers' adequate knowledge and skills in performing CIC have a positive impact on the quality of life for children by preventing UTIs 7–9 . Conversely, the lack of sufficient knowledge and skills among caregivers involved in their children's care can increase caregiver anxiety levels 15–17 . Based on this identified problem, the results of this study aimed to discuss the anxiety levels of caregivers who perform CIC on their children and the factors influencing these levels.…”
Section: Discussionmentioning
confidence: 99%
“…The following were inferred from the questions' contents and coded: relationship of the questioner with the ALS patient, gender of the patient with ALS, and question period. The main questions of the messages were coded and categorized according to the classification scheme developed in previous studies (Hucl & Spicak, 2016; Stavroulakis et al, 2016; Suluhan, Yildiz, Surer, Fidanci Eren, & Balamtekin, 2020).…”
Section: Methodsmentioning
confidence: 99%